Developing English Textbook for First Grade Students in Elementary School - Eka Shintia Hardiyanti (Graduate Program, University of Islam Malang, 2019)
AbstractThe availability of inappropriate English textbook for the first grade of elementary school students became the main problem for the students and the teachers teaching in elementary school. The existing elementary books for the first grade of elementary school students were considered too difficult for the students and it made the students not interested in learning English. This study is conducted to develop an English textbook for the first-grade students of SDN Pamaroh 1 Pamekasan. The research involves the students of the first grade of elementary school, English teacher and three experts. The development is based on the result of a need survey that shows the unavailability of the standard competence and basic competence in English for the first grade of elementary school students in SDN Pamaroh 1 Pamekasan. The procedure of the study is involving some ways: conducting a need survey, developing materials, experts validation, revising, trying out the materials, revising and getting the final product. The instruments in the need analysis consist of questionnaires, an interview guide, and field notes. The data from the students is calculated in percentages and those from the English teacher and from the field notes are described in a qualitative way. The data from the need survey is used as the basis for the materials development. A validation form is used to collect the experts judgment on the materials. The experts validate the materials in terms of the content of language and the textbooks design. The data from the experts are analyzed and described qualitatively. The try out is conducted to know the products practicality and the effectiveness of the materials. The subject is the students of the first grade of elementary school students. The final product is in the form of a textbook. There were instructions and some interesting features related to the topic in every section. It makes the teaching and learning process easy and fun.Keywords: English textbook, first grade of elementary school students.